Synergistic effects of dry-brush compatibility and shear stress on rapid alignment of lamellar microstructures for block copolymer reflectors - Yuan Xiang; Wei-Tsung Chuang; Yeo-Wan Chiang (Giant, 2024)
Because of the high viscosity of severe chain entanglements, a time-consuming process of aligning microstructural orientation in high molecular-weight (Mw) block copolymer photonic crystal films imposed limitations on efficient mass production. In this study, the effective alignment of the block copolymer microstructures in the film state can be carried out within approximately a few minutes. This achievement was realized through the synergistic localized compatibility of dry brush and shear stress during the spin-casting process. The orientation and orderliness of the microphase-separated lamellar structure in as-spun poly(styrene)-block-poly(4-vinylpyridine) (PS-b-P4VP) films can be meticulously controlled by introducing blends with PS homopolymer (hPS) of varying Mws (Mw,hPS) and cholesteric liquid crystal mesogen (Chol). Within the ternary blended films of hPS/PS-b-P4VP(Chol), the wet-brush miscibility by blending low-Mw hPS with a small molecular weight ratio (α) of Mw,hPS to Mw,bPS (Mw of the PS block chain) of α <1 results in the formation of disoriented lamellar structures, whereas dry-brush localization by introducing high-Mw hPS with α∼0.9 yields highly parallel-aligned lamellar structures to the substrate after spin casting, even with a massive quantity of additive hPS (∼59 wt%). The dry-brush compatibility can be demonstrated by morphological observation in the ternary blended film after extraction of the hPS. As a result, without any further efforts, such as additional solvent or thermal annealing treatments, the as-spun ternary blended film can exhibit visible structural colorations with controlled wavelengths by alternating the quantity of hPS. This provides an accessible solution for rapidly producing flexible photonic crystals featuring tunable photonic band gaps.